Program Kerja Pemerintah Gampong Bernuansa Islami di Gampong Aneuk Glee, Aceh - Rizkina, Cut Ridha; Fakhruddin (Jurnal Riset dan Pengabdian Masyarakat, 2022)
In a gampong or village, it really needs services that have Islamic nuances in order to be able to solve all social problems and improve the religious life that exists in the village. The criteria that exist in leadership and the need for leaders who have human values ​​which are values. Work program that supports the development and development of an Islamic life. The purpose of this research is shown to see the work program of the village apparatus with Islamic nuances in the Aneuk village. In addition, this research finds the importance of interaction between communities so that this friendship can continue. This research uses qualitative methods, the data obtained by using several data methods, namely direct interviews and observations. The results showed that the village government of Aneuk Glee did not actually carry out an Islamic work program but only continued what had been done by previous figures. So in that case, Gampong Aneuk Glee tries to provide Islamic activities to raise a better generation.